If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(3x) + 5 + -7 = 56 Remove parenthesis around (3x) 4x * 3x + 5 + -7 = 56 Reorder the terms for easier multiplication: 4 * 3x * x + 5 + -7 = 56 Multiply 4 * 3 12x * x + 5 + -7 = 56 Multiply x * x 12x2 + 5 + -7 = 56 Reorder the terms: 5 + -7 + 12x2 = 56 Combine like terms: 5 + -7 = -2 -2 + 12x2 = 56 Solving -2 + 12x2 = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 12x2 = 56 + 2 Combine like terms: -2 + 2 = 0 0 + 12x2 = 56 + 2 12x2 = 56 + 2 Combine like terms: 56 + 2 = 58 12x2 = 58 Divide each side by '12'. x2 = 4.833333333 Simplifying x2 = 4.833333333 Take the square root of each side: x = {-2.198484326, 2.198484326}
| -3x+7=5-4x | | -6x-13=-61 | | 9=5+9b | | 6l+3l=5.4 | | sin(5x)=3sin(3x) | | 8-9x=21x-7 | | y=f(-x) | | 2x-13=12-3x | | 6a-2b=32 | | -8-9x=21-7 | | y=f(x)-8 | | -1.8=-.6 | | 9(t-8)/4 | | (4y-9)(5-y)=0 | | -3-x=4-2x | | 10=a(20+23)(20-17) | | 280=x(2x+6) | | (1/x-1/6x)^-1 | | -6=-7p+2+8p | | 5(r+a)-5= | | y=f(x-8) | | 9(y+4)=5(y-4) | | (((4x)^-5)(6x)^-2)/((3x)^-3 | | a+4.9=7.6 | | -20+2x=5-3x | | 6x(-7/2) | | -20+2x=3+5 | | u/9 = 8 | | y=f(x+8) | | 6(13-5s)=62 | | 2y^2+8y+55=0 | | 24-7x=17-6x |